Edukasi kesehatan Gggi dan mulut dengan metode game pada guru TK - Siti Fatimah; Widyandana Widyandana (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Dental and oral health education of children through games among kindergarten teachersPurposeThis study aims to determine the differences of knowledge about the dental and oral health of children before and after instruction with the game method called “Rangking I” among kindergarten teachers. MethodsThis research was a quasi experimental study with quantitative data analysis using a one group experimental design. A total of 29 kindergarten teachers were educated by the game method called “Rangking 1”. Changes in knowledge before and after education were measured using a pre-test and post-test. ResultsThe Wilcoxon test showed that education with the “Rangking 1” game method and lectures can be effective in improving the knowledge of kindergarten teachers related to oral and dental health. ConclusionThe game method “Rangking 1” can increase the knowledge of dental and mouth health in kindergarten teachers significantly. Schools need to consider implementing learning methods through games for kindergarten children.